ac Bubble Electrospinning Technology for Preparation of Nanofibrous Mats - Erben, Jakub; Kalous, Tomas; Chvojka, Jiri (ACS omega, 2020)
This study deals with a new combination of alternating current (ac) electrospinning and bubble electrospinning. Research devoted to the combination of these two methods for the preparation of nanofibrous and microfibrous mats has been carried out. The design, construction, and description of bubble electrospinning are described in this article. The final morphologies of the fibrous layers produced by these methods have been compared with other well-known electrospinning methods. The bubble electrospinning and ac electrospinning aspire to become new technologies that could be utilized in various technical areas and tissue-engineering applications.